THE IMPORTANCE OF LEARNING MEDIA TO INCREASE STUDENTS' INTEREST IN LEARNING IN STUDY PRIMARY SCHOOL IPAS LEARNING - Silvina Noviyanti; Muhammad Sofwan; Arum Desta Widyawati; Zahratul Jannah; Cahya Karina (Jurnal Scientia, 2023)
Learning media can increase students' interest in learning, especially in IPAS and IPAS learning. Where learning media can support the learning process to be more effective and efficient. The aim of this research is to determine the importance of learning media to increase students' interest in learning in IPAS and technology subjects in elementary schools. The research method used in this research is qualitative, with the type of research namely description. This research uses data collection techniques, namely observation and interviews. The results of this research were obtained from the use of learning media to increase students' interest in learning in elementary school IPAS and IPAS subjects, which had an influence on the learning process for both teachers and students so that IPAS and IPAS learning could achieve the planned learning objectives. Before implementation, there needs to be planning in advance which is seen from the needs and characteristics of students which are adapted to the IPAS learning material, so that the implications obtained from learning can be more active and effective, learning is centered on students and learning objectives can be achieved.